French horn solos - TSCHAIKOWSKY, P.I. [et.al] (Amsco Music Publishing Co., 1942)
A frangesa....P. CostanAbide with me......W.H. MonknAdeste fidelis......J. ReadingnAh!So pure from martha......Friederich Von FlotownAmerica..S.F. Smith